Comprehensive characterization and comparison of aroma profiles of rambutan seed oils using GC-MS and GC-IMS combined with chemometrics - Zhou, Yanchi; Cui, Jingtao; Wei, Qiaozhu; Wu, Long; Li, Tian; Zhang, Weimin (Frontiers in Nutrition, 2024)
Aroma significantly influences the quality of rambutan seed oil. This study systematically investigated and compared the aroma characteristics of three types (BR-4, BR-5 and BR-7) of rambutan seed oils using HS-SPME-GC-MS and HS-GC-IMS techniques, augmented by chemometric modeling. GC-MS identified 135 volatile compounds, primarily hydrocarbons and esters, while GC-IMS characterized 35 compounds, mainly aldehydes and alcohols. Multivariate statistical analyses revealed significant differences in the aroma profiles among the oil samples. BR-5 exhibited the highest levels of aldehydes and hydrocarbons, whereas BR-7 demonstrated the highest content of esters and ketones. 21 and 15 differentially volatile compounds were extracted from the datasets obtained via GC-MS and GC-IMS. These compounds primarily comprised esters (floral and fruity) and aldehydes (green and fatty), interacting to create the distinctive aroma profiles of the three rambutan seed oils. This study provides theoretical support for evaluating the flavor characteristics and utilization potential of rambutan seed oil.